Kesedaran kepelbagaian dan hubungan dengan tingkah laku dalam kalangan staf sokongan Universiti Teknologi Malaysia, Skudai - Isnin, Nurin Hamizah (2014)
Diversity is an important topic in this globalization era. Before understanding diversity, we need to have diversity awareness since it will influence our way of thinking and behaving which will be displayed through our attitudes. Diversity awareness is important to workers working in any industries especially education since it is needed to provide service and communicate well with diverse international students. If higher diversity awareness level, then the service provided will be good but if the diversity awareness level is lower, then a program or an activities that will increase awareness should be implemented. The diversity awareness will influence one’s behavior. So the problems occur are what is the level of diversity awareness among support staff, what is the relationship between dimension of diversity awareness and behavior, what is the relationship between the entire diversity awareness and behavior, and lastly, will diversity awareness influence behavior towards international student’s diversity. Therefore the objectives are to determine level of diversity awareness among support staff, the relationship between dimension of diversity awareness and behavior, the relationship between the entire diversity awareness and behavior and also the influence diversity awareness give to behavior. Questionnaire has been prepared and being distributed to support staff in UTM, Skudai. The outcomes of the research are the level of diversity awareness is medium; there are positive relationship between dimension of diversity awareness and behavior, there are significance relationships between the entire diversity awareness and behavior and diversity awareness influence behavior.